THE QUALITY IMPROVEMENT OF EDUCATION: IMPLEMENTATION, DEVELOPMENT, AND HUMAN RESOURCES - Larasati, Novi (International Journal Multidisciplinary (IJMI), 2024)
This article discusses the implementation of strategies and practices for the development of Human Resources (HR) in school environments with the objective of increasing the quality of education. Quality education requires competent, committed teachers and staff, and continuing education to develop themselves. This study focuses on the initiative of human resource development in schools to support the achievement of optimal quality education. This article discusses how to develop human resources (HR) to improve the quality of education in schools. The enhancement of the quality of education is based on research and is achieved through internal human resource development planning that is based on a variety of needs and a tiered cadre system. This text reports on a qualitative research study that investigated various strategies implemented by schools for human resource (HR) development, including training, coaching, and leadership development programs. The research findings indicate that the implementation of HR development in schools has a positive impact on the quality of education. The study found that participating teachers in the development program showed enhanced competence and motivation in teaching. Apart from that, coaching leadership among staff in schools has also contributed to an improved atmosphere and school culture. In conclusion, this research serves to find that investing in human resource development in schools can be an effective strategy to increase the quality of education. The practical implications of this study can guide policy makers and education practitioners in designing and implementing sustainable HR development programs in school environments. Keywords : Management, development, human resources.